TINJAUAN PENGELOLAAN KEUANGAN DESA DAN IMPLIKASINYA TERHADAP AKUNTABILITAS - Duwi Agustina (Universitas Pendidikan Nasional, 2019)
AbstrackThe purpose of this study was to examine empirically the effect of Village Apparatus capacity, organizational commitment, implementation of Village Financial System (SISKEUDES) and supervision of Badan Permusyawaratan Desa toward the village financial management. This study also aims to determine the effect of village financial management on the accountability in Banyu Asin Village, Riau Silip Sub-district, Bangka Regency. The data used in this study are primary data obtained directly by distributing questionnaires to village officer involved in village financial management, consisted of Village Government, Badan Usaha Milik Desa (BUMdesa) and Lembaga Pemberdayaan Masyarakat (LPM). The sample of research were taken by saturation sampling method (census) amounts 50 respondents The statistical analysis uses SmartPLS 3.2.8 program with PLS-PM (Path Modelling) structural equation model. The result of this research showed that the capacity of village apparatus has a positive and not significant effect on village financial management, organizational commitment has a positive and significant effect on village financial management., implementation of village financial system (SISKEUDES) has a positive and significant effect on village financial management, and supervision of Badan Permusyawaratan Desa has a positive and significant effect on village financial management. Other than that, village financial management has a positive and significant effect toward accountability.